2014
DOI: 10.1016/j.sbspro.2014.11.116
|View full text |Cite
|
Sign up to set email alerts
|

Examining Leadership Competencies during Economic Turmoil

Abstract: The paper aims to present results of study examined leadership competencies during the economic turmoil in Lithuania, Latvia, Cyprus and Bulgaria. Challenges and change of generations conditioned by economical situation suppose re-thinking on leadership competencies and the need for purification of priorities while educating young leaders. The research indicated that leadership competencies consist of three blocks: (1) self-management competencies, (2) business management competencies and (3) people management… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
3
0
1
Order By: Relevance
“…The results of research conducted by Bhardwaj & Punia [22], Khoshouei, Oreyzi, & Noori [23], Savaneviciene, Ciutiene, & Rutelione [24], Ali & Mortazvi [25] can be concluded that creative industries can grow and develop not only because have quality products, but also must be supported by management and qualified human resources.…”
Section: Review Of Literature 21 Creative Industrymentioning
confidence: 99%
“…The results of research conducted by Bhardwaj & Punia [22], Khoshouei, Oreyzi, & Noori [23], Savaneviciene, Ciutiene, & Rutelione [24], Ali & Mortazvi [25] can be concluded that creative industries can grow and develop not only because have quality products, but also must be supported by management and qualified human resources.…”
Section: Review Of Literature 21 Creative Industrymentioning
confidence: 99%
“…A systematic framework on leadership competencies with a focus on crisis situations is defined by Savanevičienė et al (2014). The framework defines 1) self-management (SM) competencies which help leaders to "be stable in unspecified environment and to adapt to rapidly changing circumstances" on an individual level and 2) people-management (PM) competencies "which allow warranting of efficient people management".…”
Section: Crisis Leadershipmentioning
confidence: 99%
“…A good leader will serve his society and advance his nation. So they have to develop leadership and managerial skills [3][4] [5][6] [7] especially in turmoil economic conditions [8]. Research related to the role of leaders in national growth after the second world war was reviewed by Jones and Olken in year 2005, which stated that there was a high causative relationship between the role of the leader and the economic development of the country [9].…”
Section: Literature Review 21 Leadership and Development Performancementioning
confidence: 99%